Surmounting the summit: tackling cerebral malperfusion in AMDS-treated acute deBakey I dissections. A case report - de Manna, Nunzio Davide; Helms, Florian; Deniz, Ezin; Kaireit, Till Frederik; Abu-Fares, Omar; Schmack, Bastian; Ruhparwar, Arjang; Weymann, Alexander; Popov, Aron Frederik (Frontiers in Cardiovascular Medicine, 2024)
Background Acute Type A aortic dissection (ATAAD) with supra-aortic branch (SAB) malperfusion remains a formidable clinical challenge, often resulting in high mortality and complex treatment dilemmas. The introduction of the AMDS represents a significant innovation, designed to stabilize the aortic arch, and manage malperfusion effectively. Methods This case study evaluates the utility of AMDS in the treatment of a 63-year-old male with hypertension, who presented with severe, acute chest pain. Diagnosed with a DeBakey type I ATAAD involving SAB, the patient underwent cardiopulmonary bypass, aortic root replacement, aortic arch repair with AMDS implantation, and subsequent endovascular stenting for severe left common carotid artery malperfusion that developed postoperatively. The AMDS was instrumental in facilitating crucial aortic arch reconstruction and addressing the initial severe malperfusion. Despite postoperative cerebral malperfusion, targeted endovascular stenting resulted in a rapid and substantial neurological recovery. The patient was discharged to a rehabilitation facility on postoperative day 20, free of neurological deficits. Conclusions The use of AMDS in managing ATAAD with SAB involvement is transformative, enabling less invasive surgical techniques and offering immediate, effective correction of malperfusion. This case underscores the essential role of integrating advanced endovascular strategies to enhance outcomes in high-risk aortic surgeries, marking a pivotal advancement in the therapeutic approach to complex aortic dissections.